Corpo-inço: resistência e metamorfose através do autorretrato fotográfico - Griss, Audrian Vinicius Cassanelli (2023)
The present research in Visual Arts has its roots in my origin in the interior and is based on the observation of existing weeds in the surroundings of the monocultures of the locality of Xanxerê-SC. The weeds resist and adapt to conditions hostile to life and make my existence different from others where my body is seen as a weed. Thus, corpo-inço is a body thought through art in a poetics that seeks to verify possible relations of the weeds with the artist's body that, unwanted in its environment, resists. Corpo-inço is a body that resists because art is also resistance through what it metamorphoses, reveals and questions. With digital photography I make self-portraits that, hybridized, I see myself as another. Reality is intertwined with the artist's imagination in the series carried out in this poetic research. Current technology facilitates assimilations and crossings that change the paradigms of contemporary photography and, on the other hand, submits us to the effects of technology, making us hybrids in the use of technological devices. In my art work, this relationship with technology enables the process of establishing a work where the hybridized body evokes resistance relative to neglect, to prejudice in daring to be different, to be LGBTQIAP+ within a conservative state. Corpo-inço, doubles of myself, place of establishment and reflection that has ORLAN as an artistic reference that also puts its body at the service of art, questioning beauty, the situation of women in today's society, among other issues fundamental to existence. I seek to clarify the issues that emerge from directing with authors such as Emanuele Coccia, Vandana Shiva and Julia Kristeva to outline the issues mentioned above.